Preparation of glyburide nanocrystals with improved dissolution properties by dry-ball- and wet-bead- milling: Systematic comparison by experimental design of the performance of the two methods - Mura, Paola A. (2024)
The effectiveness of dry-ball and wet-bead nano-milling methods in producing nanocrystals of glyburide with increased dissolution rate has been compared. A full factorial design was applied to both methods to systematically evaluate the effect of the most critical factors (milling time, milling speed, ball/bead volume, drug amount) on the responses to be optimized (particle size and dissolution rate). Different experimental conditions were found to obtain the best results: the dry-method required to increase frequency and milling time and reduce ball volume and drug amount, while the wet-method to increase milling rate and drug amount and reduce bead volume and milling time. The results obtained under the respective optimal conditions evidenced a similar performance in nanocrystal production (120 and 180 nm for dry-ball and wet-bead milling, respectively) while a higher % dissolved at 10 min (28 vs 14 %) was found for the wet-method, principally ascribed to the presence, in this case, of the solubilizing polymer P188, added as stabilizer. Differently from the wet-method, the dry-method showed no direct relationship between particle size reduction and drug dissolution rate increase. Solid-state studies evidenced a role of the drug crystallinity loss, caused by the dry-milling, in affecting dissolution rate and proved the stability of the drug under both the milling processes.